TESTING THE FRAUD PENTAGON THEORY ON FRAUDULENT FINANCIAL REPORTING IN THE BANKING SECTOR INDONESIA 2016-2020 - Irmawati, Farida; Nawirah, Nawirah (Akuisisi : Jurnal Akuntansi, 2022)
Fraudulent financial reporting is an activity that is carried out intentionally by changing the elements in the financial statements. This study aims to examine and analyze the influence of the elements of the fraud pentagon theory, namely pressure, opportunity, rationalization, capability, and arrogance against fraudulent financial reporting which is proxied by using the Altman z-score model. This research is a quantitative research using secondary data, namely financial reports, and annual reports. The population of this study is the banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling method used the purposive sampling technique to 34 samples. The technique for analyzing data is through multiple linear regression. The results showed that financial stability had a positive effect on fraudulent financial reporting. External pressure has a negative effect on fraudulent financial reporting. Ineffective monitoring, quality of external audit, change in auditor, changes in the board of directors, CEO duality, and a frequent number of CEO's pictures has no effect on fraudulent financial reporting.